The Interplay between Media and Child Abuse in Pakistan: Causes, Social Impact, and Policy Responses - Muhammad Faiq Butt; Muhammad Ahsan Iqbal Hashmi; Javaria Rafaqat; Hafiz Muhammad Haseeb Ulla (Research Journal of Psychology, 2025)
Child abuse is any human-caused behavior that cease a child’s inherent potential. It involves all forms of sexual, physical, and emotional abuse that may harm a child’s development and sense of self. It has become a significant global issue, many developed and developing nations face this challenge. According to media reports, 800 innocents in Pakistan were sexually abused in 2019. Qualitative method is used for current research, and information has been obtained through variety of sources including research Articles, newspapers, magazines and books. The main fact is that right children are abused every day, which has become a serious problem for Pakistan. The current research is conducted on child abuse its types, effects, causes, role of media, educational institutions and UNCRC.